A Conductive Crosslinked Graphene/Cytochrome C Networks for The Electrochemical and Biosensing Study - A. K. M., Kafi; M. M., Yusoff; Choucair, Mohammad; Crossley, Maxwell J. (Springer, 2017)
The direct electrochemistry of catalytically active cytochrome C (Cyt c) adsorbed together with a 3-dimensional network of chemically synthesized graphene on glassy carbon electrode has been readily obtained in aqueous phosphate buffer. Direct electrical communication between the redox center of Cyt c and the modified graphene-based electrode was established. The modified electrode was employed as a high-performance hydrogen peroxide (H2O2) biosensor. The Cyt c present in modified electrode exhibited a pair of quasi-reversible redox peaks with a midpoint potential of −0.380 and −0.2 V, cathodic and anodic, respectively. Investigations into the electrocatalytic activity of the modified electrode upon hydrogen peroxide exposure revealed a rapid amperometric response (5 s). Under optimized conditions, the linear range of response to H2O2 concentration ranged from 5 × 10−7 to 2 × 10−4 M with a detection limit of 2 × 10−7 M at a signal-to-noise ratio of 3. The stability, reproducibility, and selectivity of the proposed biosensor are discussed in relation to the morphology and composition of the modified electrode.